Análisis de la competitividad del sector aeronáutico y aeroespacial de México en el mercado internacional - Meraz Rodríguez, José Antonio (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In Mexico there are some studies on the aeronautical and aerospace industry, but in relation to the analysis of competitiveness in this sector is a subject that has not been studied very much, there is scarce information about the global competitive level occupied by Mexican companies in this industry. The objective of this research is to analyze the factors that influence the competitiveness of the aeronautical and aerospace sector of Mexico in the international market. To fulfill this purpose, it is necessary to know how factors influence: Research and Development (R&D) and High Technology, in the behavior of competitiveness. An investigation is made of the classical theories of international trade, and the concepts of competitiveness are examined. The hypothesis is that in a sector as complex as aeronautics and aerospace, R&D and High Technology directly affect the competitiveness of the Mexican sector in the world market. To corroborate the hypothesis the following methodology is used: a questionnaire of 85 items was elaborated where the dependent variable is competitiveness and the independent variables are R&D and High Technology, 56 companies of the sector were surveyed based on the scale type Likert and the results were processed with the IBM SPSS statistical program, they are studied from the measures of central tendency, frequencies, correlation and determination matrices, as well as dispersion graphs. With the results obtained we know the degree of correlation that exists between the dependent variable and the independent variables and thus check its incidence, so that all the hypotheses could be verified.

En México existen algunos estudios sobre la industria aeronáutica y aeroespacial, pero en relación al análisis de la competitividad en este sector es un tema muy poco estudiado, existe escasa información sobre el nivel competitivo mundial que ocupan las empresas mexicanas en esta industria. El objetivo de esta investigación es analizar los factores que influyen en la competitividad del sector aeronáutico y aeroespacial de México en el mercado internacional. Para cumplir con tal fin se debe conocer cómo inciden los factores: Investigación y Desarrollo (I+D) y Alta Tecnología, en el comportamiento de la competitividad. Se hace una investigación de las teorías clásicas del comercio internacional, y se examinan los conceptos de la competitividad. Se plantea la hipótesis de que en un sector tan complejo como el aeronáutico y el aeroespacial, la I+D y Alta Tecnología inciden directamente en la competitividad del sector de México en el mercado mundial. Para corroborar la hipótesis se utiliza la siguiente metodología: se elaboró un cuestionario de 85 ítems donde la variable dependiente es la competitividad y las variables independientes son la I+D y Alta Tecnología, se encuestaron a 56 empresas del sector en base con la escala tipo Likert y los resultados se procesaron con el programa estadístico IBM SPSS, son estudiados a partir de las medidas de tendencia central, las frecuencias, las matrices de correlación y determinación, así como los gráficos de dispersión. Con los resultados obtenidos se conoce el grado de correlación que existe entre la variable dependiente y las variables independientes y así comprobar su incidencia, por lo que se pudieron comprobar todas las hipótesis.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2018-0554; Investigación; Desarrollo; Alta tecnología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1066